Racial Metaphors. - Singh, Nikhil Pal (Dissent (0012-3846))
The article presents the discussion on bequest of slavery conjoined at the founding with America's vaunted claims to freedom and self-government embracing the language of colorblindness and expansive notions of institutional or systemic racism.